Follow up rates and patient interest in clinical care after mild traumatic brain injury presenting to a level 1 trauma center: a TRACK-TBI prospective cohort study - Eagle, Shawn R.; Barber, Jason; Temkin, Nancy; McCrea, Michael A.; Giacino, Joseph T.; Okonkwo, David O.; Madhok, Debbie; Yue, John K.; Zerbato, Jennifer M.; Manley, Geoffrey T.; Nelson, Lindsay D., The TRACK-TBI Investigators; et al. (Frontiers in Neurology, 2025)
Study objectiveTo evaluate the rates of clinical follow-up and patient interest in clinical follow-up within the first year of traumatic brain injury (TBI) with presenting Glasgow Coma Scale (GCS) score between 13 and 15.MethodsThis is a secondary analysis of a prospective cohort study which enrolled patients with TBI first evaluated at a 1 of 23 level 1 trauma centers (n = 1,916). At 2 weeks and 3 months, the participants were asked “have you seen any healthcare provider for your TBI?” and “if so, did it help?.” Participants also completed the Rivermead Post-Concussion Questionnaire (RPQ), Quality of Life after Brain Injury- Overall Scale (QOLIBRI-OS), and Glasgow Outcome Scale Extended for TBI (GOSE-TBI) at 2 weeks, 3-, 6-, and 12-months. Persistent symptoms were defined as 3+ symptoms worse than pre-injury levels. QOLIBRI-OS≤51 was defined as lower quality of life. GOSE<8 was defined as incomplete recovery.ResultsBy 2 weeks, 43% of participants had followed up with a clinical provider; cumulative follow-up within the first year was 63%. Overall, 61% of participants interested in clinical follow-up care reported receiving clinical follow-up care. Participants who received follow-up care reported that it helped at an 86% rate. Of those not interested in follow-up care, 42% reported receiving clinical follow-up care and 86% of those receiving care reported that it helped. Approximately 44% of participants who reported “I did not think I need follow-up” at 2 weeks had incomplete recovery (GOSE<8), 40% had persistent symptoms, and 19% had lower quality of life at 12-months post-injury.ConclusionParticipants not interested in follow-up care had high rates of poor functional recovery, persistent symptoms and lower quality-of-life at 12 months following traumatic brain injury with GCS 13–15. Education and provider emphasis on the importance of clinical follow-up after hospital discharge with TBI need to be enhanced. Prioritizing timely clinical follow-up for adult patients with TBI with GCS 13 to 15 is critical for improving rates of long-term recovery in this population.